Diagnostic Accuracy of Serology Testing for Helicobacter Pylori in Perforated Peptic Ulcer - Syed Abbas Ali Shah , Awais Ali Khan , Najam Hussain , Huma Aslam ; Naveed Abbas, Atta Ul Aleem Khalid (Journal of Rawalpindi Medical College, 2014)
Background: To compare H. pylori serology testing with histopathological biopsy, in patients with perforated peptic ulcer. Methods: This cross sectional study was performed to document the diagnostic accuracy of H. pylori serology in patients with perforated duodenal ulcer. Perforated peptic ulcer was diagnosed on the basis of history, clinical findings and presence of free gas under the diaphragm on an x-ray. All individuals fulfilling inclusion criteria underwent laparotomy. Blood samples were sent for H Pylori serology by enzyme linked immunosorbent assay. At the same time, gastric antral biopsies were taken for histopathology for H. pylori. Results: Sstudy included 191 patients with diagnosed perforated peptic ulcer at laparotomy. Majority (70.2%) were males. The mean age was 41.72 years. In majority the perforation was seen along the first part of duodenum (76.4%). H. pylori serology was positive in 69.1% patients. One hundred and thirty nine (72.8%) patients had positive histopathology for H pylori. Out of these, 92.8% also had a positive H. pylori serology. Fifty two (27.2%) patients had negative histopathology for H. pylori. Out of these 5.8% had a positive serology test. One hundred and twenty nine were true positive i-e both had positive histopathology and serology and 52 were true negative i.e., they had both a negative serology and a negative histopathology. The results were therefore correct in 94.76%. The overall accuracy of serology in comparison to histopathology was 94.76%. The calculated sensitivity, specificity, positive predictive value and negative predictive value of serology in comparison to histopathology was 92.8%, 94.5%, 97.7% and 83.9% respectively. Conclusion: A high prevalence of H. pylori infection was found in patients with perforated peptic ulcers. Overall accuracy of serology in comparison to histopathology was 94.76%. Serological testing is a useful noninvasive method for the diagnosis of Helicobacter pylori infection.